Percepções de diferentes atores sociais na definição e gênese das alterações climáticas - Ferreira, Cássia de Castro Martins (2018)
The work is a contribution to the study of perception about the concept and genesis of climate change by two societies with distinct realities, one from the city of Juiz de Fora-MGBr and another, Metropolitan Area of Porto-Pt, taking as a point of starting a questionnaire and analyzing the articles published in two newspapers G1-Br and "Jornal de Notícias"-Pt in the year 2017. From the analysis of the journalistic texts and the conduct of semi-directive interviews, it was verified that 37,5% and 79% of the population questioned in Juiz de For a and AMP responded that the main cause of climate change is anthropogenic. 100% of the news in both newspapers says that the main cause of climate change is tied to human actions. The article advances in understanding the production of discourse and the perceptions of different social actors in the definition and genesis of climate change.